The Expression of Pyroptosis-Related Gene May Influence the Occurrence, Development, and Prognosis of Uterine Corpus Endometrial Carcinoma - Huang, Xiaoling; Li, Yangyi; Li, Jiena; Yang, Xinbin; Xiao, Jianfeng; Xu, Feng (Frontiers in Oncology, 2022)
Background: Increasing evidence has demonstrated that pyroptosis exerts key roles in the occurrence, development, and prognosis of uterine corpus endometrial carcinoma. However, the mechanism of pyroptosis and its predictive value for prognosis remain largely unknown. Methods: Here, UCEC data were acquired from The Cancer Genome Atlas (TCGA) database. The differentially expressed genes between UCEC and normal cases were selected to perform WGCNA. Forty-two UCEC associated pyroptosis-related genes were identified via applying differential expression analysis. PPI analysis and gene correlation analyses were applied to explore the relationship between 21 UCEC key genes and 42 UCEC associated pyroptosis-related genes. We also calculate the expression of 42 UCEC associated pyroptosis-related genes in different grade. The immune environment of UCEC was evaluated. Furthermore, pyroptosis-related genes were filtered out by the co-expression. Univariate and a least absolute shrinkage and selection operator Cox analysis (LASSO) were implemented to accomplish a pyroptosis-related gene model. We also performed consensus classification to regroup UCEC samples into two clusters. Clinically relevant heatmap and survival analysis curve were implemented to explore the clinicopathological features and relationship between two clusters. Furthermore, Kaplan–Meier survival analysis was implemented to analyze the risk model. Results: Twenty-one UCEC key genes and 42 UCEC associated pyroptosis-related genes were identified. The PPI analysis and gene correlation analysis showed their relationship clearly. The expression of 42 UCEC associated pyroptosis-related gene in different grade was also depicted. Then, a risk model based on pyroptosis-related genes was developed to forecast overall survival among UCEC patients. Finally, Cox regression analysis verified this model as an independent risk factor for UCEC patients. Conclusions: The expression of pyroptosis-related gene may influence the occurrence, development, and prognosis of UCEC.